2018
DOI: 10.1016/j.ces.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic synthesis of metal oxide nanoparticles via the nonaqueous method

Abstract: Microfluidic synthesis allows for a good control of the particle formation conditions while minimizing the consumption of material. In this study, we exploited these advantages for the nonaqueous synthesis of TiO 2 , ZnO and CeO 2 nanoparticles in a closed micro droplet reactor which resulted in well-defined particle structures. Monodisperse droplets are generated in microfluidic flow-focusing area and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Furthermore, it was determined that the K a value for the synthesized CeO 2 nanorods was approximately 80% higher than batch synthesized particles, which is attributable to the smaller particle sizes and higher surface areas enabled by microfluidic syntheses. [96] Stolzenburg et al [97] then demonstrated the syntheses of TiO 2 , ZnO, and CeO 2 using a single microfluidic reactor and chemistry. Nanocrystals were synthesized by mixing titanium(IV) isopropoxide, zinc(II) acetylacetonate hydrate, or cerium(III) chloride in benzyl alcohol, which was then fed into a microfabricated PDMS reactor and formed into droplets via flow focusing using Fluoronox 1008 as the continuous phase.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Furthermore, it was determined that the K a value for the synthesized CeO 2 nanorods was approximately 80% higher than batch synthesized particles, which is attributable to the smaller particle sizes and higher surface areas enabled by microfluidic syntheses. [96] Stolzenburg et al [97] then demonstrated the syntheses of TiO 2 , ZnO, and CeO 2 using a single microfluidic reactor and chemistry. Nanocrystals were synthesized by mixing titanium(IV) isopropoxide, zinc(II) acetylacetonate hydrate, or cerium(III) chloride in benzyl alcohol, which was then fed into a microfabricated PDMS reactor and formed into droplets via flow focusing using Fluoronox 1008 as the continuous phase.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…However, in laminar flow conditions in straight miniaturized channels, convective mass transport perpendicular to the flow direction does not occur and mixing occurs by slower Taylor–Aris dispersion [22]. Various geometric designs for microfluidic systems were proposed to speed up the mixing, like flow-focusing or lamination mixers [23,24,25,26,27]. A further method of a more efficient mixing process is the segmentation of the continuous flow with a low miscible medium such as gas, which results in a periodic gas–liquid flow, a so-called ‘Taylor flow’ [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic systems have proven to be a great platform for the synthesis and optimization of various nanoparticles including metal and metal oxide nanoparticles, semiconductors, colloidal nanoparticles, and hybrid organic–inorganic nanoparticle composites [19,20,21,22,23]. The formation of niosomes can be achieved via microfluidics by applying a controlled laminar mixing of two or more inlet streams, whereupon precipitation of the surfactant and subsequent self-assembly into the product occur [24,25].…”
Section: Introductionmentioning
confidence: 99%